Determination of nutritional risk rate in patients hospitalized in the Gastroenterology Service at Turkey hospital - Sokulmez, Pinar; Avci, Ilknur Aydin (Progress in Nutrition, 2014)
Aim: This study aims to determine the nutritional risk of the patients hospitalized in Gastroenterology Clinic during the initial hospitalization. Methods: A questionnaire including descriptive characteristics of the 241 patients who hospitalized in the Gastroenterology Clinic and NRS-2002 to assess the nutritional status. The Friedman repeated analysis of variance was used. Results: The mean age of the patients recruited in the study was 56.60±17.7 years. 43.2% of them were male and 56.8% were female. There was no statistical difference in nutritional deterioration scoring between the first, second and third screenings. However, at the first screening, 12% and 3.7% of the patients were categorized as mildly undernourished and as severely undernourished. At the third screening, 15% were categorized as mildly undernourished and 1.7% as severely undernourished (p>0.05). Conclusion: The present study concluded that the rate of the patients at the risk of malnutrition was high.